The Influence of Capital Structure, Company Size and Profitability on Value Firm With Good Corporate Governance as a Moderation Variable in The Processed Food Sub-Industry/Processed Food Listed in Indonesia Stock Exchange (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to determine the effect of capital structure, firm size and profitability on firm value with good corporate governance as a moderating variable. This research was conducted at processed food sub-industry companies listed on the IDX for the 2019-2022 period. The population used in this research was 24 companies and there were 14 companies used as research samples. The data analysis technique and hypothesis testing used is SmartPLS 4.0.9.4 software. The results of this study indicate that the capital structure variable has no significant effect on firm value, firm size has no significant effect on firm value, profitability has a significant effect on firm value, GCG moderates capital structure on firm value, GCG has not been able to moderate firm size on firm value, GCG moderating profitability on firm value. Keywords: Capital Structure, Company Size, Profitability, Corporate Value and Good Corporate Governance.